1976
DOI: 10.1063/1.323263
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and thermal properties of Pb2Nb2O7 at low temperature

Abstract: Measurements of the dielectric constant, polarization, zero-field specific heat, and field-dependent specific heat of polycrystalline Pb2Nb2O7 at low temperatures are reported. No evidence for a phase transition at 15 K was found, contrary to previous suggestions of an antiferroelectric transition at 15 K based on dielectric data. The peak in the dielectric constant appears to be due to relaxation phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
0
8
2
Order By: Relevance
“…Our interpretation of the literature is different from that of Siegwarth et al [84], shown in Fig. 8: This is not relaxation of defects, but a relaxor ferroelectric transition.…”
Section: B Pyrochlore Reanalysis Literature Sectioncontrasting
confidence: 94%
See 3 more Smart Citations
“…Our interpretation of the literature is different from that of Siegwarth et al [84], shown in Fig. 8: This is not relaxation of defects, but a relaxor ferroelectric transition.…”
Section: B Pyrochlore Reanalysis Literature Sectioncontrasting
confidence: 94%
“…These have been interpreted as magnetically driven, but we suspect that they are typical of most pyrochlores and independent of magnetism. Siegwarth and Lawless [84] report a very small pyrochlore polarization of 6 nC cm −2 for Pb-niobate. They published details of the equipment, in 1971, with such sensitive capabilities [104].…”
Section: B Pyrochlore Reanalysis Literature Sectionmentioning
confidence: 98%
See 2 more Smart Citations
“…Many years ago a presumably ferroelectric transition was reported at T c = 15.4 K [19,20]. However, subsequent work showed that this temperature marked a relaxation onset [21]. This was before the era of relaxor ferroelectrics, and so these authors assumed that this is not a structural phase transition but merely the relaxation of a point defect.…”
Section: Hexaferritesmentioning
confidence: 99%